2016
DOI: 10.1007/s40806-016-0063-7
|View full text |Cite
|
Sign up to set email alerts
|

When Strangers Start to Gossip: Investigating the Effect of Gossip on Cooperation in a Prisoner’s Dilemma Game

Abstract: Previous research indicates gossip is a social bonding system that is use to establish shared acquaintances and/ or attitudes, to punish group norm violators, or for coercion via invoking fear of gossipmongers. However, no empirical work explores directly the relationship between gossip about freeloaders leading to improved cooperation in recipients. Thus, we predicted that the sharing of negative gossip about the freeloading behavior of a third party will lead to higher levels of cooperation. Using levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…For example, in a study of competitive intercollegiate rowers, when a teammate was not pulling his weight during various preparations for the season, teammates took it upon themselves to engage in “negative personal talk” about the slacker in ways that were adversarial, apocryphal, and (from the perspective of the speakers) humorous (Kniffin and Wilson 2005 , 2010 ). Whereas trash talk is typically about an individual’s opponents and gossip is often about fellow members of an individual’s team or organization, value is nevertheless gained by recognizing that at least one of the ways in which “trash talk” would have been discussed in the traditional anthropological record would be in the context of reporting about “gossip.” Indeed, this is especially true when one accepts a broader definition of gossip that includes statements made about others who are not necessarily part of one’s community (see De Backer et al 2016 ; Dunbar 1998 ; McAndrew and Milenkovic 2002 ; McAndrew et al 2007 ; Scalise Sugiyama 2016 for more evolutionary analyses of gossip).…”
Section: Trash-talking and Disciplinary Traditionsmentioning
confidence: 99%
“…For example, in a study of competitive intercollegiate rowers, when a teammate was not pulling his weight during various preparations for the season, teammates took it upon themselves to engage in “negative personal talk” about the slacker in ways that were adversarial, apocryphal, and (from the perspective of the speakers) humorous (Kniffin and Wilson 2005 , 2010 ). Whereas trash talk is typically about an individual’s opponents and gossip is often about fellow members of an individual’s team or organization, value is nevertheless gained by recognizing that at least one of the ways in which “trash talk” would have been discussed in the traditional anthropological record would be in the context of reporting about “gossip.” Indeed, this is especially true when one accepts a broader definition of gossip that includes statements made about others who are not necessarily part of one’s community (see De Backer et al 2016 ; Dunbar 1998 ; McAndrew and Milenkovic 2002 ; McAndrew et al 2007 ; Scalise Sugiyama 2016 for more evolutionary analyses of gossip).…”
Section: Trash-talking and Disciplinary Traditionsmentioning
confidence: 99%
“…However, if one relays (mis)information out in the open, by posting it on one's Facebook wall or tweeting it to all followers, then the context needs to be made explicit as well as the intention: is this meant to be taken as true information, as something funny, as an expression of outrage? Sharing is a pointing gesture whereby the content pointed at is deemed "shareworthy" (Arielli 2018) yet what is worthy of being shared depends on one's personal preferences as well as the intended audience. Without making clear the context with every gesture of sharing, the meaning of the gesture will become a source of confusion and can only aggravate the already destructive effects of online misinformation.…”
Section: Discussionmentioning
confidence: 99%
“…The pragmatic value of sharing is more than asserting that someone said something. To discern what is at stake in sharing, I side with Arielli (2018) who pointed out that sharing is a speech-act 'whose aim is to direct the attention of other people to a content, stating (or expressing) its shareworthiness' (Arielli 2018, p. 253). When we retweet or share a post, we are not stating that it is true, rather we are acting as conductors of our friends' attention flow; our claim is that what we share is minimally interesting for others.…”
Section: On the Ambiguity Of Norms For Sharing On Social Networking Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this, social media platforms are used to spread gossip, with commentators working as relays effectively. While evolutionary psychologists construe the role of gossip in making networks more reliable (Backer et al 2016), from a moral standpoint, gossip is primarily harmful because it excludes the subject of gossip who cannot answer to the hurtful claims in an effective manner. While some work done on gossip in social epistemology has shown that gossip can facilitate overcoming epistemic injustice by giving a voice to those who are systematically oppressed and do not have access to authoritative communication (Alfano and Robinson 2017).…”
Section: Moral Sensitivity and User Interactions On Social Mediamentioning
confidence: 99%